DELEUZE AND THE PROBLEM OF CORRELATIONISM - da Veiga, Adamo Bouças (2024)
In this paper we present a discussion about Meillassoux’s concept of correlationism in respect to Deleuze’s philosophy. The concept is developed in order to classify all the philosophies that, since Kant, as denied thought’s acess to being and the world in itself. We proceed through a compared analysis of the main papers in this discussion in order to think if Deleuze’s thought can or cannot be considered a correlationist one. The conclusion is that Deleuze’s concept of difference cannot be interpreted as a correlational. Difference, following Deleuze, is the world in itself, being only thinkable, not known, what allow us to characterize  his philosophy as post-critical and, then, tuned to various contemporary philosophical projects.